The Effect of an Infant Care Educational Program on the Stress Level of Primiparous Women - Soghra Jamshidbeiki; Mehrnaz Geranmayeh; Siyamak Tahmasebi; Zohreh Khakbazan; Abbas Mehran (Mashhad University of Medical Sciences, 2016)
Background & aim: Women experience various changes in their transition into motherhood and feel stressed while facing new challenges in this period. High levels of stress may prevent mothers from realizing their maternal role. In this study, we aimed to explore the effects of training on the stress of primiparous mothers. Methods:In this quasi-experimental intervention, 100 pregnant women were divided into control (n=50) and intervention (n=50) groups in Tehran, Iran in 2013. The intervention group received routine care, along with planned training in three sessions. The data collection tools included a demographic questionnaire, a childbirth information questionnaire, and a bisectional stress questionnaire. The stress questionnaire was completed before training and six and twelve weeks postpartum. For data analysis, repeated measures ANOVA, Chi-square test, Fisher's exact test, and t-test were performed, using SPSS version 16.0. Results: Based on the findings, no significant difference was observed between the groups in terms of demographic characteristics. However, a meaningful difference was reported in mean stress scores between the two groups at six and twelve weeks postpartum (PConclusion: Considering the effects of training on stress relief, design and implementation of educational programs for pregnant women are recommended to reduce their stress and improve their health conditions.